Comparison of Freelite™ and N Latex serum free light chain assays in subjects with end stage kidney disease on haemodialysis - Kennard, Alice; Hawley, Carmel; Tate, Jill; Klingberg, Sandra; Pretorius, Carel; Hutchison, Colin; Mollee, Peter (Clinical chemistry and laboratory medicine, 2016)
Quantification of serum free light chains (FLC) is important in the diagnosis of plasma cell diseases where an abnormal kappa:lambda ratio infers a population of monoclonal plasma cells. The Freelite™ and N Latex assays have been validated in populations without kidney disease but there is a paucity of data relating to the use of these assays in end stage kidney disease (ESKD). The aim of the study was to compare FLC assay performance in ESKD patients on haemodialysis. Cross-sectional multi-centre study comparing the performance of the two assays on 112 haemodialysis patients without known paraproteinaemia. We quantified FLC pre- and post-dialysis using both the N Latex and the Freelite assays. FLC levels were elevated by both assays. Lambda FLC levels were considerably higher by the N Latex assay. Using the proposed renal reference range for Freelite (0.37–3.1) all but one patient had normal kappa:lambda FLC ratios. In contrast, there were no abnormal FLC ratios pre-dialysis using the N Latex assay. This was due to lambda FLC reading significantly higher by the N Latex assay. Kappa and lambda FLC levels decreased with dialysis but remained elevated above the normal range. The excess of lambda FLC by N Latex persisted post-dialysis but was somewhat attenuated. Dialysis adequacy and dialysis modality predicted clearance of kappa and lambda FLC by both assays. The N Latex assay reported significantly higher pre-dialysis lambda FLC concentrations compared with the Freelite assays. Clinicians should be aware of the need for a separate renal reference range for interpreting FLC ratio using the Freelite assay but not for the N Latex assay in ESKD patients.